Selectivity of Saflufenacil for Sweet Sorghum and Potential use of Na-Bentazon as a Safener - Correia,N.M. (2015)
The objective of this study was to assess the selectivity herbicide saflufenacil for two sweet sorghum hybrids, when sprayed in preemergence and postemergence, besides the use of Na-bentazon as a 'safener' for saflufenacil. Three experiments were conducted, in pots, maintained in an ambient condition (second and third experiments) and in a greenhouse (first experiment). In each experiment a completely randomized distribution was used, with four replicates. In the first (2 x 6 factorial) two hybrids of sweet sorghum (CVSW 80007 and CVSW 80147) and six dosages (0; 35; 52.5; 70; 87.5 and 105 g ha-1) of saflufenacil were studied, applied in preemergence of the plants. In the second (2 x 5 factorial) the same hybrids of sweet sorghum sprayed in postemergence with saflufenacil (0; 35; 52.5; 70 and 87.5 g h-1) were assessed. In the third (4 x 5 factorial) the association of Na-bentazon (0; 240; 480 and 720 g ha-1) to saflufenacil (0.35; 52.5; 70 and 87.5 g ha-1) was studied, when sprayed in postemergence on the sweet sorghum plants (CVSW 80007). Hybrid CVSW 80147 was more tolerant to saflufenacil than hybrid CVSW 800007, in preemergence or postemergence applications. The variables that best assessed the sensibility of the sweet sorghum to saflufenacil were number of emerged plants, for preemergence applications, and dry matter of stem for postemergence. Na-bentazon showed promise for use as 'safener' in postemergence applications of saflufenacil in sweet sorghum for dosages up to 70 g ha-1.